An engineered mouse embryonic stem cell model with survivin as a molecular marker and EGFP as the reporter for high throughput screening of embryotoxic chemicals in vitro. Issue 7 (12th April 2019) - Zang, Ru; Xin, Xin; Zhang, Fengli; Li, Ding; Yang, Shang‐Tian
Abstract: Embryonic stem cell test (EST) is the only generally accepted in vitro method for assessing embryotoxicity without animal sacrifice. However, the implementation and application of EST for regulatory embryotoxicity screening are impeded by its technical complexity, long testing period, and limited endpoint data. In this study, a high throughput embryotoxicity screening based on mouse embryonic stem cells (mESCs) expressing enhanced green fluorescent protein (EGFP) driven by a human survivin promoter and a human cytomegalovirus promoter, respectively, was developed. These EGFP expressing mESCs were cultured in three‐dimensional (3D) fibrous scaffolds in microbioreactors on a multiwell plate with EGFP fluorescence signals as cell responses to chemicals monitored noninvasively in a high throughput manner. Nine chemicals with known developmental toxicity were used to validate the survivin‐based embryotoxicity assay, which showed that strongly embryotoxic compounds such as 5‐fluorouracil, retinoic acid, and methotrexate downregulated survivin expression by more than 50% in 3 days, while weakly embryotoxic compounds such as boric acid, methoxyacetic acid, and tetracyclin showed modest downregulation effect and nonembryotoxic saccharin, penicillin G, and acrylamide had negligible downregulation effect on survivin expression, confirming that survivin can be used as a molecular endpoint for high throughput screening of embryotoxicants. The potential developmental toxicity of three Chinese herbal medicines were also evaluated using this assay, demonstrating its application in in vitro developmental toxicity test for drug safety assessment. Abstract : A high throughput embryotoxicity screening was developed using mouse embryonic stem cells (mESCs) expressing enhanced green fluorescent protein (EGFP) driven by human survivin promoter and cytomegalovirus (CMV) promoter, respectively. In this survivin‐based embryotoxicity assay, strongly embryotoxic retinoic acid down‐regulated survivin expression by more than 50% in three days, while weakly embryotoxic boric acid showed modest down‐regulation effect and non‐embryotoxic saccharin had negligible effect on survivin expression, confirming that survivin can be used as a molecular endpoint for high throughput screening of embryotoxicants.